2018
DOI: 10.1038/s41598-018-22196-x
|View full text |Cite
|
Sign up to set email alerts
|

A cascading nonlinear magneto-optical effect in topological insulators

Abstract: Topological insulators (TIs) are characterized by possessing metallic (gapless) surface states and a finite band-gap state in the bulk. As the thickness of a TI layer decreases down to a few nanometers, hybridization between the top and bottom surfaces takes place due to quantum tunneling, consequently at a critical thickness a crossover from a 3D-TI to a 2D insulator occurs. Although such a crossover is generally accessible by scanning tunneling microscopy, or by angle-resolved photoemission spectroscopy, suc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 42 publications
2
25
0
Order By: Relevance
“…It was confirmed that both crystalline Sb 2 Te 3 and GeTe samples show a signal with a periodicity of π up to a certain thickness. 25 Nevertheless, we have observed a strong oscillation with a period of π/2 for a thin SL film, confirming the fact that the Dq k signal is not simply the sum of contributions from the GeTe and Sb 2 Te 3 layers, but comes from the interfaces of the hybridized SL structure where Dirac like-cones may exist. 16,[19][20][21] Thus, a four period oscillation having a π/2 periodicity as a function of the light helicity suggests the existence of the Dirac-like cone or surface Rashba states 35 36 This is in contrast to conventional GST225 alloy, where the IFE dominates resulting in larger C than L values leading to a two period oscillation with π periodicity.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…It was confirmed that both crystalline Sb 2 Te 3 and GeTe samples show a signal with a periodicity of π up to a certain thickness. 25 Nevertheless, we have observed a strong oscillation with a period of π/2 for a thin SL film, confirming the fact that the Dq k signal is not simply the sum of contributions from the GeTe and Sb 2 Te 3 layers, but comes from the interfaces of the hybridized SL structure where Dirac like-cones may exist. 16,[19][20][21] Thus, a four period oscillation having a π/2 periodicity as a function of the light helicity suggests the existence of the Dirac-like cone or surface Rashba states 35 36 This is in contrast to conventional GST225 alloy, where the IFE dominates resulting in larger C than L values leading to a two period oscillation with π periodicity.…”
Section: Resultssupporting
confidence: 76%
“…The extracted L and C values as a function of the GeTe layer thickness are shown inFigure 4(b). For very thin GeTe layer thicknesses, the L (OKE) value is very large and dominates the C term (IFE) (here the C value is almost negligible) giving rise to a symmetric oscillation with a period of π/2 that suggests the existence of a Dirac-like cone 25. With increasing GeTe layer thickness, the OKE contribution to Dq k decreases while the contribution of the IFE component is enhanced, resulting in a decrease in the L value and a concomitant asymptotic increase in the C value, respectively, suggesting that the Dirac-like cone approaching the band gap opening at the G point.…”
mentioning
confidence: 99%
“…N V represents NV-induced third-order susceptibility, and the last term suggests a possible contribution from the cascaded second-order susceptibility χ (2) N V [11,17,18], which may be detected by Typeset by REVT E X surface sensitive optical methods, such as optical reflectivity. Note that the second-order susceptibility χ (2) is generally zero whenever the material has inversion symmetry, i.e., in the case for high purity diamond.…”
Section: Methodsmentioning
confidence: 99%
“…1e,f (solid red curve) with 15 , 24 where σ is the excitation pulse width, and τ S is the spin relaxation time. The first and second terms describe instantaneous spin contributions of the bulk carriers 25 , 26 and non-instantaneous spin contributions of the surface carriers, respectively. Note that the y and z components of the spin-polarization are observed in the present optical configuration.…”
Section: Resultsmentioning
confidence: 99%